Preventive Allergen-Specific Vaccination Against Allergy: Mission Possible? - Tulaeva, Inna; Kratzer, Bernhard; Campana, Raffaela; Curin, Mirela; van Hage, Marianne; Karsonova, Antonina; Riabova, Ksenja; Karaulov, Alexander; Khaitov, Musa; Pickl, Winfried F.; Valenta, Rudolf (Frontiers in Immunology, 2020)
Vaccines for infectious diseases have improved the life of the human species in a tremendous manner. The principle of vaccination is to establish de novo adaptive immune response consisting of antibody and T cell responses against pathogens which should defend the vaccinated person against future challenge with the culprit pathogen. The situation is completely different for immunoglobulin E (IgE)-associated allergy, an immunologically-mediated hypersensitivity which is already characterized by increased IgE antibody levels and T cell responses against per se innocuous antigens (i.e., allergens). Thus, allergic patients suffer from a deviated hyper-immunity against allergens leading to inflammation upon allergen contact. Paradoxically, vaccination with allergens, termed allergen-specific immunotherapy (AIT), induces a counter immune response based on the production of high levels of allergen-specific IgG antibodies and alterations of the adaptive cellular response, which reduce allergen-induced symptoms of allergic inflammation. AIT was even shown to prevent the progression of mild to severe forms of allergy. Consequently, AIT can be considered as a form of therapeutic vaccination. In this article we describe a strategy and possible road map for the use of an AIT approach for prophylactic vaccination against allergy which is based on new molecular allergy vaccines. This road map includes the use of AIT for secondary preventive vaccination to stop the progression of clinically silent allergic sensitization toward symptomatic allergy and ultimately the prevention of allergic sensitization by maternal vaccination and/or early primary preventive vaccination of children. Prophylactic allergy vaccination with molecular allergy vaccines may allow halting the allergy epidemics affecting almost 30% of the population as it has been achieved for vaccination against infectious diseases.